Funcionalização covalente e não covalente de nanotubos de carbono - Feitosa, Johnny Peter Macedo (2009)
The work developed in this thesis consists in the study of the process of non covalent functionalization of carbon nanotubes with triblock and diblock copolymers and covalent functionalization of carbon nanotubes with stearic acid. The non covalent functionalization of carbon nanotubes were realized using triblock copolymer [triblock E69S15E69, E69S7E69 (E= ethylene oxide, S = styrene oxide), E65G7E65 (E = ethylene oxide, G = phenyl glycidyl ether), the diblock copolymer E20CL10 (E = ethylene oxide, CL = Ɛ-caprolactone)] e SDS (sodium dodecyl sulfate). The individualization of carbon nanotubes with copolymer and SDS, were performed by stirring, sonication and centrifugation. The resulting samples were characterized using the Raman resonant spectroscopy study, exciting in wavelength of 532 nm (2.33 eV). The photoluminescence studies, in the copolymers and SDS solution, were realized using a detector InGaAs for detecting light in the intermission of 800 – 1700 nm, and a lamp of Xe, exciting in spectral intermission of 500 – 850 nm. The characterizations were used to identify the type of semiconductors carbon nanotubes, by photoluminescence, as well as the other identified by resonant Raman spectroscopy and the aspects that showing the individualization of carbon nanotubes using copolymers matrix. The covalent functionalization of carbon nanotubes were realized using stearic acid. The functionalization was performed in three steps, carboxylation of carbon nanotubes, usingfor this the mixture H2SO4:HNO3, functionalization of carbon nanotubes with COCl groups and functionalization of carbon nanotubes with stearic acid. The characterization of the obtained sample was realized using the Raman resonant spectroscopy study, exciting with laser at wavelength of 514,5 nm (2,41 eV), FTIR, DSC, in N2 atmosphere and heating rate of 10ºC/min in the intermission of 25 – 400 ºC, and TGA, in N2 atmosphere and heating rate of 10 ºC/min with intermission 25 – 900 ºC. These characterizations were realized in order to confirm the covalent functionalization of the carbon nanotubes with stearic acid, obtaining shift in the crystalline structure of the carbon nanotubes, showed by the Raman resonant spectroscopy study and corresponding -OOC-O-COO- anhydride bond also showed in the FTIR spectroscopy, as well as change in the thermal behavior of the carbon nanotubes functionalized in comparison with pure carbon nanotubes.